Principal Leadership In Improving Teacher Performance at SMPN 1 Pasangkayu - Choiriah Muslimah Nurdin; A. Ifayani Haanurat; Andi Mappatompo (IECON: International Economics and Business Conference, 2025)
This study aims to examine how the leadership of the principal of SMPN 1 Pasangkayu can improve teacher performance. The approach used is descriptive qualitative, with data collection through interviews with the principal and teachers. The stages of data reduction, data presentation, and drawing conclusions (verification) are the stages of the data analysis process used in this study. Based on the research findings, the principal actively assists teachers in creating learning objectives, providing them with work instructions, inspiring them, and supporting their professional growth. In addition, student management and infrastructure also influence teacher performance. This study emphasizes the importance of consistent and collaborative transformative leadership in encouraging improvements in the quality of education. Based on the results of this study, it is hoped that SMPN 1 Pasangkayu will continue to strengthen participatory leadership and support teacher professional development. The principal is advised to maintain an open leadership style and respect teacher potential, while teachers are expected to be more proactive in training and professional collaboration.